HUBUNGAN RIWAYAT MENONTON AUDIO VISUAL DENGAN USIA MENARCHE PADA SISWI DI SLTP KECAMATAN KEBUMEN KABUPATEN KEBUMEN TAHUN 2011 - Indriyastuti, Hastin Ika; Hakimi, Muhamad; Ismail, Djauhar (Jurnal Ilmiah Kesehatan Keperawatan, 2015)
One of the Millennium Development Goals (MDGs) is to improve maternal and child health. To improve maternal health starts from adolescent health to women of childbearing age. An important aspect of adolescent girls’ health is reproductive health, which is characterized by the occurrence of menarche (first menstruation). Menarche is influenced by many factors, such as factors of race, ethnicity, genetic, social, economic, medicine, health, and audio visual equipment. The effects of global information (audiovisual media) which is more accessible will lure children and teenagers to adopt bad habits such as watching blue films, pornographic VCDs, porn internet access, and porn scene via mobile.The aim of this research is  to determine the relationship of the history of watching audiovisual to age of menarche among junior high school female students in Kebumen Sub-district of Kebumen District.A cross sectional survey design was used in this study. The Population was VII grade female students of 5.050 who had experienced menarche in the Junior High School Subdistrict Kebumen District Kebumen. Sampling methods use two-level clustering method. The first stage level at random cluster sample selection and the second level is a simple random elementary unit. Samples were obtained as many as 214 students selected at random proportionate sampling at each school. Data was collected through questionnaires, measurements of weight and height scales by meter. The data analysis by Chi Square test and used to know best models by logistic regression test.The results show that  mean age of menarche was 11.8 years. Most of the students (58.4%) had a history of watching audio-visual equipment. There was a significant relationship of a history of watching audio-visual (p 0.001; RP = 2.57, 95% CI = 1.68 to 3.94), socioeconomic (p 0.0001; PR = 1.77, 95% CI = 1.25 to 2.49) to the age of menarche. There was no significant relationship between chronic disease (p 0.918) and nutritional status (p 0.448) and the age of menarche. The history of watching an audio-visual was associated with age of menarche, and had 5.14 times more likely than girls who never watched any audio-visual equipment. There needs to be education about reproductive health for adolescents and supervise the use of audio-visual media in accessing porn movies. Keywords: Audio Visual, menarche, Adolescent